The Benefits of Peer Feedback in EFL Writing Learning Processes - Kristian Wijaya (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Abstract The main purpose of feedback is not merely to keep EFL learners on the right writing track but also to elevate their profound awareness concerning the common mistakes that frequently occur in designated writing texts. Thus, second language teachers need to start introducing EFL learners to the compatible use of peer feedback to enable them to undergo more seamless writing learning processes based on their strengths and weaknesses. This small-scale library study employed a thematic analysis approach to obtain more accurate, credible, and robust findings applicable to existing writing learning dynamics. Toward that end, the researcher reviewed 20 previous peer feedback and writing studies taken from various reputable journal article platforms. The researcher specifically selected these 20 previously published scientific articles as they were mutually linked with the major investigation forming in this library study. The thematically-analyzed research results suggested second language educators reckon on the optimal use of peer feedback in their regular writing learning basis as it helped EFL learners to be more confident and knowledgeable writers. Keywords: EFL writing; feedback; peer feedback; library study; thematic analysis.